Diseño e implementación de un sistema de envío de mensajes de texto para informar a la población sobre el valor a cancelar de los predios urbanos del Cantón La Maná - Neira Álava, Jorge Patricio (2017)
The present research consists of providing an information service via mass text messages using an IP communication system with the help of a GSM Gateway that allows the installation of several GSM SIM Cards to make calls or send messages in a decentralized manner From interconnected communication networks using the TCP / IP family of protocols from the Gateway, transforming the GSM network together with the internet via LAN, creating a hybrid IP network at less cost, directed to particular cellular destinations. With the implementation of this system, which is initiated by performing tests to rule out hardware incompatibility, a textual notification (SMS) type message will be sent to the user information about the tax to be canceled or any novelty of some kind such as arrears , Meetings, data updates etc. Through this system, the user will be previously informed, of which the employees of the department of appraisals and cadastres of GAD La Maná will stimulate the process of information of a textual type to the users, obtaining information on this tax to cancel the institution from the comfort of Their mobile phones. Thus achieving a use of this innovative technology with the help of a Gateway using a sophisticated specialized system for communication is based on free software called Elastix Version (open source software for unified communications.), Which allows the sending of messages individually And massive, in order to provide comfort to the user giving him an up-to-date and fast information.